(untitled) (Boletin Médico de Postgrado, 2025)
Plants are found in nature, in homes, schools and gardens; their uses can be ornamental, but they are also used for medicinal and curative purposes. The predominant age group for toxic exposures to ornamental plants are children from 2 to 3 years of age, the usual routes of exposure being digestive and mucocutaneous. The following is the case of a pediatric patient with poisoning by Aleurites sp plant studied and diagnosed in the Pediatrics Service of the Hospital Br. Rafael Rangel in Yaritagua, Yaracuy State, Venezuela, with the corresponding literature review.